All’s (or Not) Fair in Work and Life? Focus on Females in Information and Communications Technology Through the Prism of Work-Life Balance - Wiza MUNYEKA; Ashika MAHARAJ (CECCAR Business Review, 2023)

(untitled)
The changing nature of employment and work has resulted in new demands and challenges in society, such as work-life balance, that have developed in labor relations as an imperative aspect of a beneficial work environment. Scholars affirm that implementing work-life balance practices aid in achieving better organizational results and improve employee outcomes like satisfaction, commitment and reduced turnover intentions. However, some authors have argued that there are variances between the availability of work-life balance practices in corporations and employees’ perceptions of access to such practices. This study’s purpose was to explore the professionals’ perceptions of work-life balance on managing career and personal life at a telecommunications company. This study adopted a qualitative semi-structured interview method to gather data from 16 participants selected through a purposive sampling method. The results indicated that participants agreed that when they thought about work-life balance, it meant controlling their work and life aspects, like personal interests, family, social and leisure, resulting in a balance over life and work and them being happier and more productive. This study unveiled different perceptions of female information and communications technology professionals. Reflecting that, the study emphasized the advancement of work-life balance practices to encourage and modify employees’ perceptions.